Antisemitism in the Visual Culture of Medieval Iceland: From the Vatnsfjörður Psalter to Teiknibókin - Jennifer Laura Stewart 1998- (2023)
Evidence of antisemitism in the literature, poetry, and artwork of medieval Iceland may be identified through a study of the Icelandic manuscripts and the cartographic depictions of Iceland that have survived from the 12th to early 17th centuries. The research on the visual representations of Jews and the reception of Jewish people in medieval England can serve as a basis for the interpretation of the materials that remain from Iceland’s medieval period. The history of antisemitism in medieval Iceland can be investigated through a visual analysis of the negative, racialised images of Jews recognised in the caricatures of Jewish people and the illustrations of symbolic beasts from medieval Iceland and northern Europe in the Codex Upsaliensis, the Physiologus, the Teiknibók, and the Vatnsfjörður Psalter, and in the cartographic examples of monsters found in the waters of Guðbrandur Þórkalsson’s 16th century map of Iceland, Abraham Ortelius’ copy from the late 16th century, Matthias Quad’s map from the early 17th century, and Petrus Kaerius’ version from the 17th century. An examination of the medieval Icelandic visual culture suggests that the antisemitic attitudes that were introduced to Iceland from abroad became firmly rooted in the medieval Christian worldview of the Icelanders. Vísbendingar um gyðingahatur í bókmenntum, ljóðum og listaverkum Íslands á miðöldum má finna með rannsókn á íslenskum handritum og kortamyndum af Íslandi sem varðveist hafa frá 12. til byrjun 17. aldar. Rannsóknir á sjónrænum myndbirtingum gyðinga og móttöku gyðinga í Englandi á miðöldum geta verið grunnur að túlkun á þeim efnum sem eftir eru frá miðaldatíma Íslands. Hægt er að rannsaka sögu gyðingahaturs á Íslandi á miðöldum með sjónrænni greiningu á neikvæðum kynþáttamyndum af gyðingum sem þekkjast í skopmyndum af gyðingum og myndskreytingum af táknrænum dýrum frá miðalda Íslandi og Norður-Evrópu í Codex Upsaliensis, Teiknibókin, og Vatnsfjarðarsálmarinn, og í kortagrafísskum dæmum um skrímsli sem finnast í sjónum á Íslandskorti ...